FOSSIL CONIFER WOODS FROM CERRO PICHE GRABEN (TRIASSIC-JURASSIC?) NORTH PATAGONIAN MASSIF, RÍO NEGRO PROVINCE, ARGENTINA (Ameghiniana, 2018)
Fossil conifer woods are described for the first time in sedimentary rocks from Cerro Piche Graben, North Patagonian Massif, Argentina. The permineralized axes are chacaracterized by a pith constituted by parenchyma cells and a few sclerenchyma cells; secondary xylem homoxylic and pycnoxylic, without distinct growth rings; tracheid pits uniseriate and mainly spaced; cross fields cupressoid, with 3 to 8 pits; and rays homocellular, uniseriate and low. Based on these characteristics, the woods are assigned to Cupressinoxylon. Until now, the only fossil plants known from Cerro Piche were two specimens of Pleuromeia sp., which are reinterpreted also as conifer fossil remains.